1978
DOI: 10.1128/aac.14.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Two Transport Systems for Tetracycline in Sensitive Escherichia coli : Critical Role for an Initial Rapid Uptake System Insensitive to Energy Inhibitors

Abstract: Escherichia coli sensitivity to tetracycline involves transport and accumulation of the antibiotic within the cell by two different uptake systems: an initial rapid uptake, which occun over the initial 6 min of contact of the cell with tetracycline, and a slower uptake system, which continues indefinitely and whose rate of uptake is 1/10 that of the rapid system. Only the slow uptake system is blocked by inhibitors of energy-driven systems; it appears to be particularly dependent upon energy from oxidative pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…This implies that other factors, including immunological, are involved in the establishment and maintenance of the chronic Q-fever disease syndrome. The NM and PRS isolates possess distinct plasmids (13,22,23); the S Q217 isolate lacks free plasmid DNA (although it contains plasmid DNA integrated into the chromosome (1,4,7,10,16). In our studies, we found that L929 mouse fibroblasts persistently infected with different isolates of C. burnetii differentially accumulated [3H]tetracycline (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…This implies that other factors, including immunological, are involved in the establishment and maintenance of the chronic Q-fever disease syndrome. The NM and PRS isolates possess distinct plasmids (13,22,23); the S Q217 isolate lacks free plasmid DNA (although it contains plasmid DNA integrated into the chromosome (1,4,7,10,16). In our studies, we found that L929 mouse fibroblasts persistently infected with different isolates of C. burnetii differentially accumulated [3H]tetracycline (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…An energy-dependent accumulation of the tetracyclines occurred in susceptible E. coli ML3Q8-225 grown in medium A and assayed in phosphate buffer; subsequent blocking of energy production by the uncoupler 2,4-dinitrophenol (DNP) caused the drug to flow out of the cells (e.g., see minocycline, Fig. 1A) (21)(22)(23). However, when the same strain was grown in L broth before being assayed in buffer, minocycline and tetracycline accumulation was much smaller, and the addition of DNP either decreased the uptake very little or, particularly in the case of minocycline, actually increased uptake (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore propose that most of the tetracyclines which accumulate in these cells exist in at least three cellular compartments: the membrane, the ribosome, and the efflux system. Furthermore, since binding is reversible (3,21,22), it is likely that membrane-bound drug is in equilibrium with that on the ribosomes. Most of the active net uptake seen in cells grown in minimal media may also represent increased bound drug and not free drug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that the uptake of tetracycline by Lforms is only slightly sensitive to DNP. As pointed out by McMurry and Levy (20), E. coli displays two tetracycline uptake kinetics, the first one DNP insensitive and the second inhibited by DNP. The kinetics of tetracycline uptake by the parent Listeria strain appears to be biphasic with a rapid binding insensitive to DNP up to 10 min of incubation.…”
Section: Discussionmentioning
confidence: 99%